NEWS OF VIOLENCE IN POSMETRO PADANG DAILY, A STUDY OF DISCOURSE ANALYSIS - Sari, Nia; Rahmat, Wahyudi; Samsiarni, Samsiarni (Journal of Pragmatics and Discourse Research, 2021)
Problem of this research is rise of violent cases that occurred in the community, and this news is widely published in social media, one of them is Posmetro Padang. This research aims to describe the analysis of violent news discourse on Padang Posmetro. This type of research is a qualitative study using descriptive methods. The data source of this research is Padang Posmetro, which was published from January 2020 to November 2020. The data in this study were violent news posted by Posmetro Padang. Data is collected, then read and recording techniques. The results of data analysis show that, first, text structure. The text can explain in terms of headlines. The headlines are well emphasized, such as describing the news's setting, details, and content as a whole text. Second, view the location, situation, events, and social conditions. Third. Social Context News about violence has often appeared every year. The growing discourse in the people of West Sumatra regarding the news of violence varies. Many elements are involved in this issue, so the form of the information also goes in terms of sides. In addition, this problem that often arises makes West Sumatra people more introspective. As a complete analysis of discourse on news of violence, it can be seen that the public must be alert to any crime that is happening at this time.